2010
DOI: 10.1080/10874208.2010.501498
|View full text |Cite
|
Sign up to set email alerts
|

Neurofeedback Effects on Evoked and Induced EEG Gamma Band Reactivity to Drug-Related Cues in Cocaine Addiction

Abstract: Introduction Preoccupation with drug and drug-related items is a typical characteristic of cocaine addicted individuals. It has been shown in multiple accounts that prolonged drug use has a profound effect on the EEG recordings of drug addicts when compared to controls during cue reactivity tests. Cue reactivity refers to a phenomenon in which individuals with a history of drug abuse exhibit excessive psychophysiological responses to cues associated with their drug of choice. One of the aims of this pilot stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 103 publications
2
44
0
1
Order By: Relevance
“…Patients receiving neurofeedback showed significantly more improvements in outcome measures (e.g., of hypochondriasis, obsessing, interpersonal sensitivity, aggression, psychosis, anticipation of positive outcome, and desire to use drugs) and on QEEGs. Preliminary research (Horrell et al, 2010) has suggested that neurofeedback may also have potential to reduce drug cravings in cocaine abusers.…”
Section: Alcoholism and Substance Abusementioning
confidence: 99%
“…Patients receiving neurofeedback showed significantly more improvements in outcome measures (e.g., of hypochondriasis, obsessing, interpersonal sensitivity, aggression, psychosis, anticipation of positive outcome, and desire to use drugs) and on QEEGs. Preliminary research (Horrell et al, 2010) has suggested that neurofeedback may also have potential to reduce drug cravings in cocaine abusers.…”
Section: Alcoholism and Substance Abusementioning
confidence: 99%
“…Lastly, the biofeedback group failed to show the elevated beta-endorphin serum levels, which are related to stress, that was seen in AUD patients undergoing traditional treatment (Peniston and Kulkosky 1989). A study by Horrell et al (2010) investigated a combined intervention of neurofeedback with motivational interviewing in cocaine abusers. The neurofeedback training aimed to increase sensorimotor rhythm (SMR) amplitude and/or decrease theta band frequency.…”
Section: Neuromodulatory Techniques For Treatmentmentioning
confidence: 94%
“…Following treatment completion, the participants showed increased SMR amplitude while managing to maintain the theta band levels at a stable level. In a cue reactivity task after neurofeedback, participants decreased EEG gamma activation (Horrell et al 2010). In a second study also using a combination of EEG neurofeedback and motivational interviewing in cocaine abusers, the treatment group showed the typical P300 amplitude decrease seen in retest (Stotts et al 2006).…”
Section: Neuromodulatory Techniques For Treatmentmentioning
confidence: 98%
“…Therefore, many researchers use the wavelet transform for biological signal analysis (Adeli, Zhou, & Dadmehr, 2003;Gandhi, Panigrahi, & Anand, 2011;Gandhi, Panigrahi, Bhatia, & Anand, 2010;Ghosh-Dastidar, Adeli, & Dadmehr, 2007;Horrell, El-Baz, Baruth, Tasman, & Sokhadze, 2010;Hu, Wang, & Ren, 2005;Jahankhani, Kodogiannis, & Revett, 2006;Sparto, Parnianpour, Barria, & Jagadeesh, 2000). For example, Adeli et al (2003) used discrete Daubechies and harmonic wavelets to study epileptic EEG signals.…”
Section: Introductionmentioning
confidence: 99%
“…Ghosh-Dastidar et al (2007) applied a wavelet transform to decompose EEG signals into delta, theta, alpha, beta, and gamma frequency subbands. Horrell et al (2010) used a wavelet transform for extracting the gamma rhythm from EEG signals. Gandhi et al (2010) investigated epileptic and seizure-free EEG signals of the same person using wavelet transform.…”
Section: Introductionmentioning
confidence: 99%